2014
DOI: 10.1002/jls.21314
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Praxis, and Reflection: The Three Critical Elements of Effective Leadership Studies Programs

Abstract: Th e articles in this special symposium of the Journal of Leadership Studies off er a wide range of models for leadership education, from the very old-close, refl ective reading of Plato, Aristotle, and other ancient thinkersto the very new-intensive instruction in engineering skills. Yet, across all the diff erent perspectives, from the liberal arts and social sciences to agricultural education, engineering, and cocurricular learning programs, a common core learning structure is evident, which serves to tie t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…We argue that the methods used in the current study disrupted students' thinking and their assumptions about followership. Reflection, creative drawing, and discussion also enabled them to achieve “deep personal discovery of themselves as followers” (Harvey & Jenkins, , p. 73). Furthermore, the additional focus on language provided students opportunity to (a) become aware of followership, (b) question dominant ways of thinking about followership, and (c) do followership.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We argue that the methods used in the current study disrupted students' thinking and their assumptions about followership. Reflection, creative drawing, and discussion also enabled them to achieve “deep personal discovery of themselves as followers” (Harvey & Jenkins, , p. 73). Furthermore, the additional focus on language provided students opportunity to (a) become aware of followership, (b) question dominant ways of thinking about followership, and (c) do followership.…”
Section: Resultsmentioning
confidence: 99%
“…This activity encouraged students to reflect on their own experiences of following, and to explore the concept beyond the use of language and words/terms commonly associated with it. In this exercise, students demonstrated critical thinking through reflection (Harvey & Jenkins, ) by depicting and talking about how they might use situational factors to modify their followership behaviors, and how they might differ in terms of skills and feelings when “doing following” (Morris, ) as compared with doing leading (see also Figure ). In addition to the drawings noted in Figure , students provided metaphors and symbols to convey meaning of followership such as the symbolic representations of “cutting through red tape” and “keeping your mouth zipped” (Figure ).…”
Section: Seminar Design and Drawing As Learning Methodsmentioning
confidence: 99%
“…For example, Jenkins (2018) found that the "home" program or department of leadership educators in faculty roles ranges dramatically from business to agriculture and public administration to higher education, professional health, and educational leadership. Correspondingly, subfields within specific disciplines, including social sciences, engineering, agriculture, liberal arts, business, and others, are providing "academic niches" for leadership development within higher education (Harvey & Jenkins, 2014;Harvey & Riggio, 2011;Riggio, Ciulla, & Sorenson, 2003) while discipline-specific leadership programs, whether in an undergraduate, graduate, curricular, cocurricular, or hybrid framework, provide a space and place for specific leadership competencies to be applied to specific career and industry values (Guthrie & Jenkins, 2018;Seemiller, 2013; see also Sowcik & Komives, in press).…”
Section: What Are the Domains That Leadership Educators Organize Themmentioning
confidence: 99%
“…According to Harvey and Jenkins (2014), knowledge, praxis, and reflection are the three critical elements in leadership programs, regardless of the discipline, college, program, or department facilitating the learning. Arguably, pedagogies that intentionally integrate critical thinking across these three elements will have the greatest influence on the development of learners' critical thinking dispositions and skills.…”
Section: The Critical Leadership Logic Modelmentioning
confidence: 99%